Neighborhood Park Utilization Study for Environmental Quality Improvement" Case Study: Alam Sutera Residential, South Tangerang - Olivia Seanders; Hinijati Widjaja; Titiek Poerwanti Deborah (Journal of Synergy Landscape, 2023)
The quality of the urban environment has become a major concern in various cities around the world. Rapid growth and urbanization in urban areas have had serious impacts on the quality of air, water and other environmental aspects. In this context, Neighborhood Park has become the focus of attention as an effort to mitigate these negative impacts and improve the quality of the urban environment. This research aims to examine the usefulness of Neighborhood Park in improving environmental quality, using a case study at Alam Sutera Housing, South Tangerang. Through field data collection, interviews, and data analysis, this research attempts to identify possible positive impacts associated with Neighborhood Park within this region. Factors such as their impact on air quality, water quality, carbon sequestration, and community social welfare are also explored. It is hoped that the results of this research will provide valuable insights for stakeholders in Alam Sutera Housing and similar urban areas. This study also contributes to global understanding of the important role of Neighborhood Parks in addressing the challenges of the modern urban environment. With an emphasis on the development and maintenance of sustainable green open spaces, this research provides a basis for taking better action to support environmental quality and community well-being in rapidly growing urban areas.